Шляхи розвитку правового регулювання електронних довірчих послуг у міжнародних актах UNCITRAL - Костенко, Олексій Володимирович; Костенко, О. В.; Kostenko, Oleksii V.; Костенко, Вікторія Володимирівна; Костенко, О. В.; Kostenko, Viktoriia V. (Одеса, 2018)
У статті проаналізовано законодавчий досвід правового регулювання суспільних відносин у сфері цифрового підпису й електронних довірчих послуг Комісії ООН із міжнародного торговельного права Міжнародної торгової палати і Європейської економічної комісії UNCITRAL. Вивчаються перспективи правового регулювання визнання транскордонних довірчих послуг і цифрових підписів шляхом розроблення загальних, стандартизованих міжнародних правових актів Робочою групою IV Комісії, а також за участі багатьох країн світу. Сьогодні в ЮНСІТРАЛ формується загальне уявлення вирішення проблеми транскордонного визнання іноземних цифрових підписів та електронних довірчих послуг на основі умови застосування хоча б одного з доктринальних тлумачень і наявності двох рівнів безпеки. Опрацьовано пропозицію Російської Федерації щодо запровадження проекту «Вдосконалення системи управління ідентифікаційними даними під час використання транскордонного простору довіри й загальної інфраструктури довіри в застосуванні до транскордонних електронних комерційних угод». Вивчено пропозиції Австрії, Бельгії, Італії, Сполученого Королівства Великобританії та Європейського Союзу стосовно можливості встановлення узгоджених рівнів безпеки, які забезпечуються за допомогою довірчих послуг, і рівнів правових наслідків. Також розглянуто пропозиції щодо застосування принципів взаємного транскордонного визнання для довірчих послуг, що мають однаковий рівень безпеки, і застосування правового режиму відповідальності для кваліфікованих постачальників довірчих послуг. Узагальнено проблеми транскордонного використання цифрових підписів та електронних довірчих послуг, притаманні країнам із різною юрисдикцією. Досліджені перспективні напрями міждержавного врегулювання сфери цифрових підписів та електронних довірчих послуг на основі прикладів і пропозицій окремих країн.

Introduction of new forms of international cooperation, namely, electronic cross-border cooperation, is one of the priority directions of development of the world community. Electronic cross-border co-operation, including the use of cross-border trusted services, needs legislative regulation today. One of the locomotives of the international law-making process in the field of electronic trust services, electronic signatures is the United Nations Commission on International Trade Law, the International Chamber of Commerce and the Economic Commission for Europe (UNCITRAL, Commission). UNCITRAL approved the Model Law on Electronic Commerce and the Model Law on Electronic Signatures with a Guide to Enactment 2001. These legal acts became the classic basis for the creation of normative and legal acts of almost all countries in the field of e-commerce and electronic signature, laid the general principles of cross-border recognition of certificates of electronic digital signature. Starting in 2014, the UNCITRAL Working Group IV on e-Commerce has taken steps to address legal issues related to the management of identity and trust services. UNCITRAL is considering the process of legal recognition of trust services and digital signatures as a requirement for identifying legal requirements and establishing relevant substantive law in any jurisdictional system However, at the current stage of development of international and national law in the area of using trust services and digital signatures in the cross-border regime, a number of global problems remain unresolved. The problem of terminology. The problem lies in the fact that national laws or international laws contain a set of concepts and definitions that are significantly different and sometimes of an overly technical nature, which complicates the perception of ordinary citizens. The problem of credential as a component of a digital signature and trust services. As you know, the key components of a digital signature are subscriber data, which is considered as digital credentials. To date, no legislative act addresses the issues of cross-border recognition of digital credentials, namely: who should hold such recognition, which party they should be recognized as the purpose of such mutual recognition, which features should be available for mutual recognition, which restrictions may apply during mutual recognition. Also, outside the scope of legal regulation, there is currently a problem of the mutual recognition of identity data of legal entities, digital devices or digital objects. The problem of trust in electronic services and digital signatures. The possibility of introducing technical mechanisms for ensuring the reliability of trust services exists and can be implemented promptly. However, today there are no international legal mechanisms guaranteeing a certain level and standards of trust in digital services of one of the parties exchanging such services. In many national identification systems, including in Ukraine, so-called “levels of security of trust” are defined as in the European Union (“low”, “high” and “basic”). While four levels of trust are used in the United States and in some other countries. The problem of cross-border interoperability. States with different legal culture traditionally diverge in the technical and legal assessment of digital signatures. Common Laws (United States, United Kingdom) do not impose specific technical and legal requirements for a digital signature, nor does it require the mandatory provision of a digital signature at the same time by all parties to the trust service or electronic document. In this case, an electronic signature may be created by anyone and by any technology. In Roman-Germanic legal systems (mainly in European countries), where the legal doctrine traditionally played an essential role, another concept of digital signature has developed. In order to address these issues, Working Group IV, the United Nations Commission on International Trade Law, the International Chamber of Commerce and the Economic Commission for Europe, with the participation of many countries of the world, are exploring the prospects for legal regulation of the recognition of cross-border trust services and digital signatures through the development of common, standardized international legal acts. In its activities, UNCITRAL plans to explore the experience of several projects in the field of electronic trust services: – European Commission, Regulation (EC) No. 910/2014 of the European Parliament and of the Council of 23 July 2014 on electronic identification and trusted services for electronic transactions within the internal market and repealing Directive 1999/93/EC; – The Eurasian Economic Union, the Eurasian Economic Union Treaty and the Concept for the use of services and legally significant electronic documents in inter-state information interaction; – Asia-Pacific Region, Pan-Asian Alliance for Electronic Commerce Development. Also, Working Group IV examines the existing international instruments aimed at ensuring the mutual recognition of transnational legal effects in the paper environment, such as the Convention, which abolishes the requirement for legalization of foreign official documents “Convention on Apostille” (The Hague, October 5, 1961) and the Protocol on the Uniform Order acting on behalf of the executing authority (Washington, February 17, 1940), which may include appropriate recommendations for minimum elements for the cross-border mutual recognition of UID and trust services. The issue of legal recognition of cross-border trust services has received sufficient attention from different countries. Thus, the Russian Federation proposed a project “Improving the Identity Management System in the Use of Cross-Border Confidence and Common Trust Infrastructure in the Application of Cross-Border Electronic Commerce Agreements”. The project is based on the model defined in the Model Law “On Transborder Information Exchange of Electronic Documents” of November 25, 2016. According to the project, it is proposed to create a large cluster of vertically integrated “cross-border trust”, which will have three levels of electronic trust services (basic, medium, high). The cluster can have a single international regulator, regulators of intergovernmental unions and national regulators of digital trust services and digital signatures. It is also envisaged to introduce legal levels of regulation of digital trusted services on one or many domain-based basis with the involvement of a third independent trust party, as well as the unification of international and national regulatory frameworks. Instead, the United States considers it necessary in the near future to consider the issue of legal recognition of identification information that has been authenticated in connection with a commercial transaction, namely, that it is a legal recognition of its purpose, requirements, legal support, etc. The proposals of Austria, Belgium, Italy, the United Kingdom of Great Britain and the European Union concern the possibility of establishing agreed levels of security, which are provided through trust services: the first level – with the use of unskilled trust services. The second level with the use of qualified trusted services. The second level of legal consequences will include assimilation, presumption, transfer of the burden of proof to the opposing side, as well as the principle of mutual cross-border recognition for trusted services with the same level of security. Ukraine, as an active member of the global digitalization process, is taking some steps towards updating the legislation on digital signatures and trust services, namely the introduction of the new Law of Ukraine "On Electronic Trust Services". Ukraine, by amending existing legislation, adapts the regulatory framework in accordance with Regulation (EC) No910/2014 of the European Parliament and of the Council of 23 July 2014 on electronic identification and trusted services for electronic transactions within the internal market and repealing Directive 1999/93/EU. Today, there are many national and regional concepts and initiatives in the field of trust services, which have already been well developed. They can identify the relevant issues and can serve as a basis for developing an appropriate legal framework at the international level that could be transferred to various existing legal systems. The UNCITRAL Working Group IV on e-Commerce is implementing measures aimed at achieving the following objectives: – promotion of the development of international trade law and the satisfaction of the needs of economic actors in instruments that provide legal certainty for electronic transactions committed by them; – facilitating the harmonization of new legal aspects of projects, within which these issues are currently being resolved at the national or international level, to the more specific and functional content of the general requirements formulated in the current texts of UNCITRAL; – establishing a common legal framework for trust services and digital signatures, including relevant provisions aimed at developing international cross-border operational cooperation in the legal and technical fields. It is expedient for law-makers of Ukraine to take into account the world experience in developing normative legal acts regulating the sphere of trust services and digital signatures, including in the cross-border regime.
Костенко О. В. Шляхи розвитку правового регулювання електронних довірчих послуг у міжнародних актах UNCITRAL / О. В. Костенко, В. В. Костенко // Часопис цивілістики : наук.-практ. журн. / редкол.: С. В. Ківалов (голов. ред.), Є. О. Харитонов (заст. голов. ред.), К. Г. Некіт (відп. секр.) [та ін.]. - Одеса, 2018. – Вип. 31. – С. 36-44.
Keywords: цифровий підпис; електронні довірчі послуги; транскордонний режим електронних довірчих послуг; визнання іноземних сертифікатів цифрових підписів; digital signature; electronic trusted services; cross-border electronic trust services; recognition of foreign certificates of digital signatures; Research Subject Categories::LAW/JURISPRUDENCE; Research Subject Categories::TECHNOLOGY